2015
DOI: 10.1016/j.celrep.2015.10.021
|View full text |Cite
|
Sign up to set email alerts
|

FGF21-Mediated Improvements in Glucose Clearance Require Uncoupling Protein 1

Abstract: Fibroblast growth factor 21 (FGF21)-mediated weight loss and improvements in glucose metabolism correlate with increased uncoupling protein 1 (Ucp1) levels in adipose tissues, suggesting that UCP1-dependent thermogenesis may drive FGF21 action. It was reported that FGF21 is equally effective at reducing body weight and improving glucose homeostasis without UCP1. We find while FGF21 can lower body weight in both wild-type and Ucp1 knockout mice, rapid clearance of glucose by FGF21 is defective in the absence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 13 publications
4
49
0
Order By: Relevance
“…The discovery of thermogenic adipose tissue in adult humans, once thought to be absent after infancy, has fueled interest to promote thermogenesis in multiple metabolic disorders 20, 48, 49 . Evidence that thermogenically active brown fat promotes glucose disposal 50 and, arguably, consumption of lipids 51 are among the points of logic behind the concept. Indeed, it has evolved that cold exposure is now often viewed as a natural approach to improved metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of thermogenic adipose tissue in adult humans, once thought to be absent after infancy, has fueled interest to promote thermogenesis in multiple metabolic disorders 20, 48, 49 . Evidence that thermogenically active brown fat promotes glucose disposal 50 and, arguably, consumption of lipids 51 are among the points of logic behind the concept. Indeed, it has evolved that cold exposure is now often viewed as a natural approach to improved metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Although an increase in Ucp-1 expression is believed to assist browning of WAT, recent papers demonstrated that the effects of FGF21 on body weight reduction and glucose homeostasis can occur in Ucp-1 knockout mice3334. In contrast, some authors claim that FGF21 requires UCP1 to improve glucose clearance, likely involving increased UCP1-dependent thermogenesis35. Further experiments will be required to elucidate the link between FGF21 and Ucp-1 involved in beneficial effects caused by β-conglycinin.…”
Section: Discussionmentioning
confidence: 99%
“…However, these results may depend on the conditions used (e.g. lean versus obese mice) [97]. Importantly, the influences of temperature are also beginning to be recognized in other fields [98100] suggesting that housing mice at current standard laboratory conditions may actually compromise the ability to model certain human diseases.…”
Section: Types Of Adipocytesmentioning
confidence: 99%